In search of a financial model for a sustainable economy - Zioło, Magdalena; Bąk, Iwona; Filipiak, Beata Zofia; Spoz, Anna (Technological and Economic Development of Economy, 2022)
The links between the real and financial spheres are well recognized in the literature. However, under the conditions of sustainability, both the perception of the real and financial spheres, as well as the relations between them, change. The aim of this article is to show that sustainable finance has an impact on building a sustainable economy, and the model of sustainable finance increases the degree of adjustment of the financial sphere to the real economy. The research was conducted based on 86 articles. The methodology is based on log-linear models. As a result, it was proved that sustainable enterprises and finances are the factors that most frequently interact with other variables describing a sustainable economy. The study proposes the financial model for sustainable economy, this is the main novelty and contribution of the study. The original contribution of the study includes: the comprehensive analysis of the factors and relationships between sustainability, economy and finance; building a triple layered finance model for sustainable economy taking into account governance, society and environment from sustainable perspective; proposing the model of financing for the circular economy in terms of sustainability in terms of the process and defining the model of sustainable finance 4.0.First published online 18 May 2022